Guidelines for physical activity in children with heart disease - Sejal Suresh Shah; Sweta Mohanty; Tanuja Karande; Sunita Maheshwari; Snehal Kulkarni; Anita Saxena (Wolters Kluwer Medknow Publications, 2022)
Justification : In recent years, there has been increasing recognition of children with heart disease in our country. These children belong to different age groups and have untreated, partially treated, or completely treated heart disease. The role of physical activity for optimal physical, emotional, and psychosocial well-being for children is well understood. There is a challenge for the parents and the medical professionals to take a decision regarding the type of physical activity safe for the child as heart disease may affect the hemodynamic demands. Most of the existing international guidelines focus on competitive sports in operated heart disease children. This may be of limited use when we have a mixed population of children with heart disease, different types of sports in our country and where a larger subset is looking for recommendations to leisure time activities. Process : The Pediatric Cardiac Society of India decided to formulate recommendations for physical activity in children with heart diseases. A committee of experts, who were well-versed with the subject of physical activity in children with heart disease, volunteered to take up the task of writing the guidelines. The recommendations emerged following deliberations of the committee members, on the virtual platform as well as mails. The final version of manuscript was approved by all committee members and all members are co-authors of this manuscript. The different types of physical activities were defined including leisure sports and competitive sports. The exercise was classified based on the mechanical action of muscles involved into dynamic and static components. Each type of exercise was then classified based on the intensity into low, medium, and high. Recommendations for the type of physical activity for individual heart lesions were decided based on the rationale available. Objectives : The recommendations here are made with an intention to provide general guidelines for physical activity in children with operated and unoperated heart diseases, not excluding a need for individualizing a plan, serial assessment, and comprehensive checkup in special situations. Recommendations : We hope the recommendations mentioned below would provide basic clarity in planning physical activity in children with heart disease. This is with the hope to encourage physically active life, at the same time ensuring a safety net.